Enhancing Students’ Creative Thinking Skills in Equilibrium and Rotational Dynamics Through The Implementation of Project Based Learning Modules - Noorhalida, Noorhalida; Santiani, Santiani; Annovasho, Jhelang (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
The world of education requires students who are able to create and develop new ideas. Creative thinking needs to be done, because it can improve the quality of student learning. Project-based learning is an effective learning model for encouraging creative thinking. By implementing PjBL in the classroom, teachers can help students achieve success in the future. This research aims to determine the increase in creative thinking of high school students with project learning modules on balance and rotation dynamics. This research is quantitative descriptive. The method used is one-group pre-test – post-test design. Data collection techniques use questionnaires, observations and tests. This research was carried out at SMAN 5 Palangka Raya class XI MIPA 3 with three meetings. The research results show that: 1) The learning tools in the research are very suitable for use with a value of 0.85 for the module, 0.80 for the RPP and 0.92 for the questions. 2) The learning model implemented can be implemented very well, as seen from the percentage of implementation sheets for 3 meetings of 100% in the first meeting, and 91.6% in the second and third meetings which is categorized as very good, 3) There is an increase in creative thinking in students SMA from the use of project learning modules, balance material and rotation dynamics seen from the pre-test and post-test data which shows the calculated t value < t table.